2020
DOI: 10.1515/tnsci-2020-0117
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis characteristics of gut microbiota in cerebral infarction patients

Abstract: AbstractObjectiveThe aim of this study is to investigate the dysbiosis characteristics of gut microbiota in patients with cerebral infarction (CI) and its clinical implications.MethodsStool samples were collected from 79 CI patients and 98 healthy controls and subjected to 16S rRNA sequencing to identify stool microbes. Altered compositions and functions of gut microbiota in CI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 36 publications
(35 reference statements)
2
40
0
Order By: Relevance
“…All the nine clinical studies reported on gut microbiome, where most of the clinical studies were conducted in both case and control cohorts [ 14 18 , 20 , 25 , 26 ], except that Boaden et al [ 24 ] who studied on stroke patients. All studies collected fecal samples from the study subjects for microbiome analyses and blood samples for blood biochemical assays, except that Li et al [ 16 ] collected the fecal samples and Boaden et al [ 24 ] collected the saliva sample and swabs within the oral cavity of stroke cases.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the nine clinical studies reported on gut microbiome, where most of the clinical studies were conducted in both case and control cohorts [ 14 18 , 20 , 25 , 26 ], except that Boaden et al [ 24 ] who studied on stroke patients. All studies collected fecal samples from the study subjects for microbiome analyses and blood samples for blood biochemical assays, except that Li et al [ 16 ] collected the fecal samples and Boaden et al [ 24 ] collected the saliva sample and swabs within the oral cavity of stroke cases.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical studies found that the abundance of phylum Firmicutes is an independent predictor for ischemic stroke risk [ 16 18 , 25 ]. Particularly, genera Streptococcus , Lactobacillus and Prevotella were descent from phylum Firmicutes prevailed among ischemic stroke cases [ 16 18 , 25 ]. Boaden et al [ 24 ] found that Streptococcus species were the most abundant microbiota that made up 70% of the oral microbial community in stroke patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations